(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article investigates the usage of idiomatic expressions in English language, shows usage of them in everyday conversation, shows a number of most commonly used idiomatic expressions and the meaning of them. English people use some idioms in their everyday speech while interacting with their family members, colleague, friends and so on including daily conversation. They can be called as “The most commonly used idioms of English people”. I have tried to show a small number of them. Besides them, I have learned some idioms used by famous writers in his works including the names of animals and origin of some idiomatic expressions.